Constitutive Akt1 signals attenuate B-cell receptor signaling and proliferation, but enhance B-cell migration and effector function - Pierau, Mandy; Marx, Alexander (European journal of immunology, 2012)
Ligation of the BCR induces a complex signaling network that involves activation of Akt, a family of serine/threonine protein kinases associated with B-cell development, proliferation, and tumor formation. Here, we analyzed the effect of enhanced Akt1 signals on B-cell maturation and function. Unexpectedly, we found that peripheral B cells overexpressing Akt1 were less responsive to BCR stimuli. This correlated with a decrease in Ca2+-mobilization and proliferation, in an impaired activation of Erk1/2 and mammalian target of rapamycin (mTOR) kinases and poor mobilization of NFATc1 and NF-κB/p65 factors. In contrast, activation of STAT5 and migration of B cells toward the chemokine SDF1α was found to be enhanced. Akt1 Tg mice showed an altered maturation of peritoneal and splenic B1 B cells and an enhanced production of IgG1 and IgG3 upon immunization with the T-cell independent Ag TNP-Ficoll. Furthermore, mice homo-zygous for Tg Akt1 showed a severe block in the maturation of B-cell precursors in BM and a strong enrichment of plasma cells in spleen. Altogether, our data reveal that enhanced Akt1 signals modify BCR signaling strength and, thereby, B-cell development and effector function.
Gesehen am 05.11.2018